Framing Paradise Online: A Multimodal Discourse Analysis of Destination Narratives on France Travel Website - Afdal, Taufik; Zein , T. Thyrhaya; Maharani, Puan (LingPoet: Journal of Linguistics and Literary Research, 2025)
Tourism promotion increasingly relies on digital platforms where destinations are framed through carefully constructed narratives. Using a multi modal discourseanalytical approach, the present study seeks to examine textual and visual element from lonelyplanet website, particularly the destination of France to represent tourist destinations as idyllic “paradises.” The analysis reveals that destinations are frequently framed through metaphors of escape, authenticity, and exclusivity, highlighting natural beauty and cultural uniqueness while downplaying local challenges or complexities. Additionally, multimodal resources—such as imagery, layout, and interactive features—play a central role in reinforcing persuasive narratives that align with global tourism imaginaries. Findings suggest that online tourism discourse constructs not only desirable places but also particular identities for travelers, positioning them as explorers, culture seekers, or luxury consumers. This study contributes to tourism discourse research by demonstrating how digital travel platforms commodify places through strategic language and multimodality, shaping both destination branding and tourist perceptions.